TRADISI UMPAN KAMPUNG BAGI MASYARAKAT DI DUSUN TEMURAK DESA MELIAU HILIR KABUPATEN SANGGAU - Rosianti Rosianti; Sri Buwono (Sosial Khatulistiwa: Jurnal Pendidikan IPS, 2021)
This study aims to determine the noble values of a tradition that implied in Umpan Kampung Tradition that carried out by the community in Temurak Hamlet, Meliau Hilir Village, Meliau District, Sanggau Regency. This study used descriptive qualitative method which used field observation, interviews with local community of Temurak village, and documentation. Sources of the data that are used by the researcher were primary data and secondary data. The technique of data collection through three stages, they were: data reduction, data presentation, and making conclusion. The finding of this study showed that: the background of Umpan Kampung Tradition in Temurak Hamlet, Meliau Hilir Village, Meliau District, Sanggau Regency is to express the feeling of gratitude for the sustenance that has been received by the community. The process of Umpan Kampung Tradition started with the preparation and ended with the implementation of Umpan Kampung ceremony itself. The noble values that conveyed in the Umpan Kampung tradition are the value of deliberation, the value of mutual cooperation, the value of togetherness, the value of solidarity, and the value of religion